NMR and MD Simulations of Non-Ionic Surfactants - Gerd Buntkowsky; Markus Hoffmann (Molecules)
Non-ionic surfactants are an important solvent in the field of green chemistry with tremendous application potential. Understanding their phase properties in bulk or in confined environments is of high commercial value. In recent years, the combination of molecular dynamics (MD) simulations with multinuclear solid-state NMR spectroscopy and calorimetric techniques has evolved into the most powerful tool for their investigation. Showing recent examples from our groups, the present review demonstrates the power and versatility of this approach, which can handle both small model-surfactants like octanol and large technical surfactants like technical polyethylene glycol (PEG) mixtures and reveals otherwise unobtainable knowledge about their phase behavior and the underlying molecular arrangements.